Recycling technologies for fibre-reinforced plastic composite materials: A bibliometric analysis using a systematic approach. (August 2022) - Colombo, Beatrice; Gaiardelli, Paolo; Dotti, Stefano; Caretto, Flavio
Fibre-reinforced plastic composite materials are increasingly employed in several industries. This extensive use has resulted in a huge increase of generated waste that has to be managed without causing significant environmental issues. Recycling fibre-reinforced plastic composite materials in accordance with circular economy principles might be a way to overcome such problems. Thus, this paper aims to empirically analyse the existing scientific literature regarding recycling technologies for fibre-reinforced plastic composite materials. The main goal is to provide a holistic and comprehensive analysis of the topic, as well as research gaps and future directions following a rigorous and transparent approach. Overall, 201 articles were selected through a systematic approach and then analysed using a bibliometric analysis. Results show that this topic has been increasingly gaining momentum in recent years and that researchers have mostly carried out experimental studies on chemical and thermal recycling technologies for recovering carbon fibres. Lastly, this article provides an in-depth research agenda based on identified research gaps and an enhanced managerial grasp of this field of research.